Tahlīl al-Uslub al-Qur’āni ‘an al-Tikrār fī Surah al-Ahzāb - Himatul Istiqomah (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2022)
Repetition is a style of language that beautifies the language itself. The existence of repetition in the Qur'an becomes a miracle that can soften anyone who reads or listens to it. Therefore, the study of repetition in the Qur'an becomes important in terms of linguistics, literature, and religion. This study aims to explore the types of repetitions in both Madaniyah surahs, Al-Ahzab, through a qualitative-descriptive approach that utilizes grounded research to analyze the data. The results of the study are found as follows. There are phonological, morphological, syntactic, and semantic repetitions and their types in surah Al-Ahzab, except for sentence repetition. There are 7 types of repetitions in surah Al-Ahzab, namely: mesodiplosis, tautotes, epizeuxis, anaphora, epiphora, simploke, and epanalepsis. There are one theme repetition in surah Al-Ahzab namely Asmaul Husna Allah, Most Forgiving, and Most Merciful.